Eight weeks of coordination intervention is able to modify the heart rate variability in elderly? - Cleuber Souza Gonçalves; Natália Batista Albuquerque Goulart Lemos; Graciano Joan Xavier de Lima; Lorenna Walesca de Lima Silva; Juliana Moreira Paes Landim; André Brito Carvalho; Etevaldo Dantas Coelho Junior; Fernando de Aguiar Lemos (Journal of Physical Education (Maringá), 2020)
Several studies were registered in the literature to modulate the Heart Rate Variability (HRV) in the elderly. However they are focused on the physical ability of conditioners. Little is known about the effects that structured coordinative training in circuits can promote in the HRV of the elderly. The objective of the present study was to investigate the effect of 8 weeks of a coordinative intervention under autonomic aspects of the elderly. 26 subjects were divided into two groups. One group (N = 13) with the Coordination Approach in Circuit (CACG) and  the other group (N = 13) with the Recreational Walk (RWG). To measure HRV, a cardiofrequencimeter was used. Motor Circuit Model was used for the motor evaluation, which consisted of 8 coordinative exercises. For the evaluation of functional physical fitness, the Fullerton battery was used. After 8 weeks of intervention, both HRV variables and motor variables did not differ between groups. However, when the pre and post intervention moments were observed, only in the RWG was an increase in the variable High Frequency, 5 minutes after Motor Circuit Model. Our results indicated that eight weeks of a coordinative intervention was not sufficient to generate changes in the HRV behavior of the elderly.